Comparative analysis of the antimicrobial resistance and virulence traits in ESBL-producing-Klebsiella pneumoniae ST307 strains colonizing the gastrointestinal tract and causing a fatal bloodstream infection in a leukemia patient - Boff, Luana (2024)
Produção científica do Laboratório de Pesquisa em Infecção Hospitalar (vigente até jan/2023).